Angular dependence of direct current decay in a closed YBCO double-pancake coil under external AC magnetic field and reduction by magnetic shielding. (9th February 2017) - Geng, J; Zhang, H; Li, C; Zhang, X; Shen, B; Coombs, T A
Abstract: High T c superconducting (HTS) coils are ideal candidates in the use of high field magnets. HTS coils carrying a direct current, however, suffer a non-negligible loss when they are exposed to an external AC magnetic field. Although this phenomenon is well known, no study concerning AC magnetic field angular dependence of direct current decay has ever been shown. In this work, we experimentally investigate the direct current decay characteristics in a closed double pancake coil made of a YBCO coated conductor under external AC field. AC field of different angles with respect to the coil plane is applied. Results show that the current decay rate presents a strong angular dependence. The fastest decay occurs when the field is parallel to the coil plane, in which case the surface of the tape in the outermost layer experiences most flux variation. To reduce the decay rate, we propose wrapping superconducting tapes around the outermost layer of the coil to shield external AC field. This method significantly reduces direct current decay rate under parallel field, without affecting the perpendicular self-field of the coil.